Sedimentary environment and organic matter enrichment of the Lower Cambrian Niutitang Formation shale, western Hunan Province, China - Qingmin ZHU; Longfei LU; Anyang PAN; Jinyu TAO; Jianghui DING; Wangwei LIU; Maowen LI (Shiyou shiyan dizhi, 2021)
The Lower Cambrian Niutitang Formation shale is an extremely crucial marine source rock developed at the mid-upper Yangtze block of China. To clarify the paleoenvironment and conditions which are responsible for organic matter enrichment of the Niutitang Formation shale in South China, a systematic study of petrology, organic geoche-mistry and elemental geochemistry was carried out by focusing on the Niutitang Formation shale in Yuanling, western Hunan Province. Results showed that the paleoclimate was transforming from dry-cold to warm-wet during deposition of Niutitang Formation. The level of biological productivity, the redox properties of water and the intensity of hydrothermal activity showed a consistent trend of low-high-medium-high from the early to the late stage of deposition. Rather than being controlled by a single factor, the enrichment of organic matter in the Niutitang Formation shale was the result of the mutual configuration and coupling of multiple factors such as paleoclimate, biological productivity, water redox properties, deposition rate and hydrothermal activity. The water was shallow and oxic with a low-level of productivity in the course of deposition of the lower Niutitang Formation, which was not conducive to the enrichment of organic matter. A large-scale of Early Cambrian transgression occurred during deposition of the medium Niutitang Formation, and the associated upwelling carried extensive substances such as nutrients and sulfates entered the surface water, which promoted the blooming of algae. The anoxic-euxinic environment at the bottom water was conducive to the preservation of organic matter. Although the degree of water oxidation increased during deposition of the upper Niutitang Formation, the strong hydrothermal activity triggered by the continuous extension of South China provided rich nutrients, which kept a high-level biological productivity. Meanwhile, the relatively high deposition rate led to organic matter insufficiently degraded, resulting in rapid burial, preservation and enrichment.